1996
DOI: 10.1074/jbc.271.21.12488
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Avian Osteoclastic H+-ATPase and Bone Resorption by Tamoxifen and Calmodulin Antagonists

Abstract: We used highly purified avian osteoclasts and isolated membranes from osteoclasts to study effects of tamoxifen, 4-hydroxytamoxifen, calmodulin antagonists, estrogen, diethylstilbestrol, and the anti-estrogen ICI 182780 on cellular degradation of 3 H-labeled bone in vitro and on membrane HCl transport. Bone resorption was reversibly inhibited by tamoxifen, 4-hydroxytamoxifen, and trifluoperazine with IC 50 values of ϳ1 M. Diethylstilbestrol and 17-␤-estradiol had no effects on bone resorption at receptor-satur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
35
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 34 publications
3
35
1
Order By: Relevance
“…The altered membrane properties could shift the voltage dependence of many ion channels. Indeed, tamoxifen has been reported to shift the activity of many ion channels (11)(12)(13)(14)(15)(16). Detailed studies on the model channel, gramicidin, have shown that membrane tension (47) and surface charge (48) are critical determinants of channel activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The altered membrane properties could shift the voltage dependence of many ion channels. Indeed, tamoxifen has been reported to shift the activity of many ion channels (11)(12)(13)(14)(15)(16). Detailed studies on the model channel, gramicidin, have shown that membrane tension (47) and surface charge (48) are critical determinants of channel activity.…”
Section: Discussionmentioning
confidence: 99%
“…But it has also been reported to have many pleiotropic effects both in vivo and in vitro that cannot be explained by an interaction with the estrogen receptor (4). For example, tamoxifen has been shown to enhance drug sensitivity of multidrug-resistant cells (5)(6)(7)(8)(9), inhibit bone resorption and osteoporosis both in vivo and in vitro (10), and inhibit a number of channels, including the volume activated chloride channel (11,12) and calcium channels (13)(14)(15)(16). These effects have been attributed to inhibition of P-glycoprotein (17), calmodulin (15), and direct channel interaction (11), respectively.…”
mentioning
confidence: 99%
“…A total of 100 µg of 40-to 80-µm bone pieces, ϳ60 dpm [ 3 H]proline/µg bone, were added to ϳ3 ϫ 10 3 osteoclasts in 2-cm 2 tissue culture wells, after Blair et al [1986], but using larger bone pieces to preclude possible effects due to substrate internalization; osteoclasts attached to the substrate are demonstrated by Williams et al [1996a]. Assays were less than 7 days to avoid the effects of pre-osteoclast differentiation [Williams et al, 1996b] in mixed cultures.…”
Section: Bone Degradationmentioning
confidence: 99%
“…Isolation of osteoclast-rich cell fractions from chicken bone is detailed elsewhere [Blair et al, 1986;Williams et al, 1996a]. Briefly, medullary bone from Gallus domesticus, white leghorn hens, on a Ca 2ϩ -restricted diet, was harvested and cells were removed by vigorous washing and sieved through 110-µm nylon mesh; erythrocytes were lysed in hypotonic media and cells sedimented through 70% serum to recover bone cells.…”
Section: Cell Culturesmentioning
confidence: 99%
“…Monocytes/ macrophages induced by these factors first proliferate actively and become committed preosteoclasts, tartrateresistant acid phosphatase (TRAP)-positive mononuclear cells, which then fuse to one another to become mature multinucleated OCLs (1,4,5). These cells secrete HCl to dissolve bone into its calcium salts (1,6).…”
mentioning
confidence: 99%